Refugee Women Resettling in the United States at Mid-Life after Ethnic Cleansing - Weine, Stevan M.; Vojvoda, Dolores (Refuge: Canada's Journal on Refugees, 1997)
This is a case study of two women resettlingin the United States after survivingethnic cleansing in Bosnia and adiscussion of refugee women at mid-life.We learned about their lives throughtheir participation in testimony andbiographical interviewing. DanielLevinson's study of women's lives providesa frame for thinking about therefugee woman's life after ethnic cleansing.The mid-life refugee woman's experiencein the private and public spheresis changed by their traumas, but also bythe transition from early to middleadul thood. Her recovery will be furthershaped by the contours of her continuedadult development as will the lives ofher children.